Indications and Findings of Coronary Angiography: A Descriptive Cross-Sectional Study - Bista, Madhab; Shah, Prashant; Mehta, Ram Kumar (Birat Journal of Health Sciences, 2023)
Introduction: Coronary artery disease is an important subset of cardiovascular disease that requires timely, accurate, and cost-effective diagnosis. Among several modalities practiced to evaluate this disease; coronary angiography is the gold standard. Objective: The objective of this study was to identify indications and findings of coronary angiography among patients admitted at Birat Medical College Teaching Hospital. Methodology: A descriptive cross-sectional study conducted at Department of Cardiology, Birat Medical College Teaching Hospital from 1 September 2021 to 30 June 2022 after taking ethical approval from Institutional Review Committee (Ref No: IRC-PA-167/2078-79). A total of 202 patients were included through consecutive sampling. Data was collected on baseline characteristics, indications and findings of coronary angiography. Frequency, percentage, mean and standard deviation was calculated. Result: Maximum percentage of patients were in the age group 60-69 years (20.8% males and 16.3% females) with mean± S.D(60.1± 11.1). The most common indication for coronary angiography was angina (34.1%) and treadmill test positive (24.3%). Nearly 62% had abnormal findings. Single vessel disease was present in 25.2%, double vessel disease in 5.9% and triple vessel disease in 20.6%. Other findings were cardiac bridging (2.9%), non-critical coronary artery disease (1.9%) and in-stent restenosis (0.5%). Conclusion: The most common indication of coronary angiography was chronic stable angina and the majority had vessel diseases.